2015
DOI: 10.1155/2015/451981
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the MethyLight Assay for Assessing Aging, Cigarette Smoking, and Alcohol Consumption

Abstract: The environmental factors such as aging, smoking, and alcohol consumption have been reported to influence DNA methylation (DNAm). However, the versatility of DNAm measurement by DNAm array systems is low in clinical use. Thus, we developed the MethyLight assay as a simple method to measure DNAm. In the present study, we isolated peripheral blood DNA from 33 healthy volunteers and selected cg25809905, cg02228185, and cg17861230 as aging, cg23576855 as smoking, and cg02583484 as alcohol consumption biomarkers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…We calculated the average standard deviation, ranging between 0.010 and 0.044 ( Table A2 ). Compared to other methods like SYBR Green-based qPCR [ 30 ], pyrosequencing [ 54 ], and massively parallel sequencing [ 52 ], these values are considered low for methylation assays and are in concordance with other MethyLight studies [ 55 ].…”
Section: Resultssupporting
confidence: 71%
“…We calculated the average standard deviation, ranging between 0.010 and 0.044 ( Table A2 ). Compared to other methods like SYBR Green-based qPCR [ 30 ], pyrosequencing [ 54 ], and massively parallel sequencing [ 52 ], these values are considered low for methylation assays and are in concordance with other MethyLight studies [ 55 ].…”
Section: Resultssupporting
confidence: 71%
“…DNA methylation, one of the most studied and stable epigenetic modifications, is capable of controlling gene expression of common traits and influencing the development of aberrant health outcomes under external exposures [12]. Previous epigenomewide association studies (EWASs) based on whole blood DNA methylation have identified numerous CpG sites that are associated with aging [13], various cancers and other chronic diseases [14,15], as well as with many forms of exogenous exposures and lifestyle-related factors, such as environmental pollutants [16], body mass index (BMI) [17], alcohol consumption [18] and smoking [18,19]. DNA methylation signatures have furthermore been considered as potential indicators of mortality from specific diseases and consequently with all-cause mortality [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the ROC analysis, the AUC for the DNA methylation rate was 0.746 for habitual alcohol consumers. Although the DNA methylation rates of AHRR and HNRNPA1 did not correlate with the frequency of smoking and alcohol consumption (82) , DNA methylation at these sites seems to have the potential to monitor the lifestyle of the blood sample donors. Further analyses with more various types of tissues would be also helpful.…”
Section: Forensic Applications Of Dna Methylationmentioning
confidence: 90%
“…In an effort to establish tools to aid diagnosis and monitor treatment response by environmental exposures, Endo et al . (82) developed an assay to measure DNA methylation at smoking and alcohol consumption-associated CpGs using the MethyLight method that utilizes fluorescence-based real-time PCR technology. They selected cg23576855 in the AHRR gene as smoking and cg02583484 in the HNRNPA1 gene as alcohol consumption biomarkers and tested their specificity in 33 blood samples from healthy donors.…”
Section: Forensic Applications Of Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation